Two-Body Coulomb Problems with Sources for the J-Matrix Method (Journal of Atomic and Molecular Sciences, 2011)
The two-body Coulomb problem with sources is studied. Closed formsolutions are provided for particular non-homogeneities usedwithin the J-matrix method. The results are employed to buildanalytical solutions having incoming, outgoing and standing waveasymptotic conditions.
Keywords: coulomb problem; sources; J-matrix; non-homogeneous; hypergeometric